Foetal and Neonatal Outcome in Pregnant Women with COVID-19 - Shrestha, Rupesh; Basnet, Srijana; Shrestha, Laxman (Journal of Nepal Paediatric Society, 2020)
Introduction: The pandemic caused by coronavirus disease 2019 has adversely affected the health of all individuals including pregnant women. The susceptibility of pregnant women and their foetuses to severe acute respiratory syndrome coronavirus 2 infection is not clearly known. The objective of this review is to summarise the available evidence on foetal and neonatal outcomes of pregnant women with confirmed coronavirus disease 2019. Methods: The review was conduced by searching the PubMed and MedRxiv databases for studies reporting outcome of pregnancy with confirmed coronavirus disease from December 2019 to April 2020 using combination of terms "pregnancy", "coronavirus disease 2019", "foetal outcome" and "neonatal outcome". Only peer reviewed articles reporting outcome of pregnancy with confirmed coronavirus disease 2019 were included in the review irrespective of language. Ongoing pregnancies, induced abortion, and pregnancies without outcome were excluded from analysis. Variables extracted and analysed included gestational age at delivery, mode of delivery, foetal and neonatal outcome. Results: In total, 21 studies consisting 230 pregnant women including three twin pregnancies were enrolled in the study. Fever and cough were the most common symptoms reported in pregnant women. One hundred and sixty-two (70.4%) pregnant women underwent cesarean section and there were 68 (29.6%) preterm deliveries. Eight babies tested positive out of 161 newborns that were tested for coronavirus infection. Among adverse outcomes reported, there were two miscarriages, two still births and only one neonatal death. Conclusions: Outcome of pregnancy with coronavirus disease 2019 in late trimester appears to be favourable. Occurrence of preterm delivery and cesarean section appear higher among infected pregnant women in comparison to general population. There was no conclusive evidence of vertical transmission.